A three-dimensional plasmonic spacer enables highly efficient solar-enhanced membrane distillation of seawater - Ang, Huixiang Edison (2021)
Herein, we demonstrate an energy-efficient means for water desalination using a three-dimensional (3D) porous spacer for plasmon-enhanced solar membrane distillation (MD). This unique spacer rationally designed from noble metals, which generates 60 l m⁻² of fresh water per day, had a photothermal efficiency of 98% (under 0.8 sun).